Serum Procalcitonin Level Is Associated with Positive Blood Cultures, In-hospital Mortality, and Septic Shock in Emergency Department Sepsis Patients - Webb, Amanda L (Cureus, 2020)
This study examines the accuracy of initial and subsequent serum procalcitonin (PCT) levels in predicting positive blood cultures, in-hospital mortality, and development of septic shock in emergency department (ED) patients with severe sepsis. This study includes all patients who presented to our ED with an admission diagnosis of severe sepsis over a period of nine months. The median initial PCT was 0.58 ng/mL, interquartile range (IQR) 0.16-5.39. The median subsequent serum PCT was 2.1 ng/mL, with an IQR of 0.3-11.1. The PCT trend over the initial three hours increased in 67% of the study population. Blood cultures were positive in 38% of the cohort. The median maximum PCT in those with a negative blood culture was 1.06 ng/mL compared to 4.19 ng/mL in those with a positive blood culture (p=0.0116). Serum PCT levels >2.0 ng/mL display significant correlation with positive blood cultures, in-hospital mortality, and development of septic shock and as such may serve as a biomarker for more serious infections.